POLA PEMBERIAN MAKANAN PADA BALITA STUNTING DI SAWAN, KABUPATEN BULELENG - Lina Anggaraeni Dwijayanti; Ni Sayu Putu Sri Adnyani (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2019)
Introduction: The prevalence of stunting in Indonesia is still quite high, one of which is caused directly by inadequate nutrient intake. Nutritional intake in children is largely determined by the pattern of feeding provided by the mother or family. This study aims to determine the pattern of feeding given by mothers or families to toddlers in Sawan, Buleleng Regency. Method: this research is a quantitative descriptive study with cross-sectional approach conducted on 48 families with stunting toddlers and 48 families with normal toddlers. Data were collected using a questionnaire and analyzed descriptively using SPSS Statistics 20. Results: in toddlers stunting feeding patterns performed by families, most of the menu preparation did not vary (64.6%), food processing was done incorrectly (66, 7%), unattractive food serving (62.5%), when feeding was irregular (60.4%), at the time of eating most of the children were not accompanied and supervised (77.1%) and toddlers were given distilled food before eating (64.6%). Conclusion: the pattern of feeding provided by mothers or families who have stunting toddlers is still not quite right and not in accordance with those recommended by the Ministry of Health. Key words: pattern of feeding, stunting